CGIAR and OPAPRU sign MOU to study climate action and peacebuilding in the Philippines - Medina, Leonardo; Savelli, Adam (2025)
On November 5, 2025, at the fifth Peace Research Conference organized by the Office of the Presidential Adviser on Peace, Reconciliation, and Unity (OPAPRU) in Manila, a key milestone was reached toward integrating climate resilience into the Philippines’ peacebuilding agenda. CGIAR Climate Security, part of the Alliance of Bioversity International and CIAT, and OPAPRU formally signed a Memorandum of Understanding (MoU) to advance joint research and policy collaboration on the intersection of climate, peace, and security across the Philippines. The agreement was signed by Secretary Carlito G. Galvez, Jr, Presidential Advisor on Peace, Reconciliation, and Unity (OPAPRU) and Adam Savelli, Regional Lead for Asia-Pacific (CGIAR Climate Security), marking the beginning of a formal collaboration between the institutions.